Complete criteria to be information professional / Akmal Shahmeen Ahamad Sabarudin and Naqiuddin Abd Haris - Ahamad Sabarudin, Akmal Shahmeen; Abd Haris, Naqiuddin (Faculty of Information Management, 2015)
This article discusses about the criteria to be a complete information professional as each of these criteria need to be emphasized by the employer so that the organization can be successful in their respective fields. Therefore, the information professional must have various added values and benefits such as soft skills and knowledge to be able to compete with others. Therefore, there are many criteria to be great information professional and the most important is competent, capable, compatible, commitment, character, culture and communication.